Administrative Data Automation of Civil Engineering Study Program Using Progressive Web Apps at Riau University - Nining Setia Ningsih; Muhammad Jazman; Eki Saputra; Muhammad Afdal (P3M Politeknik Negeri Bengkalis, 2023)
The Department of Civil Engineering, University of Riau has a Final Assignment Administration service. The Final Assignment Administration service procedure currently implemented is still done manually. Starting from the registration data collection for Proposal Seminars, Results Seminars, and Thesis Defence, data processing was carried out using Microsoft Excel. The amount of data that has been processed so that the processing is done too long. Likewise in Microsoft Excel where formula changes often occur so that the data is not readable. Therefore, the Thesis Administration System was built using the Progressive Web Apps (PWA) method. The system built facilitates administrative services in the Civil Engineering Study Program at the University of Riau. The built system can be accessed on various devices, using the add to home screen feature which speeds up installation, and can be accessed offline. Testing of this system uses the Black Box method, which is to prove that the functional system is running properly and correctly. The results of this test are 100% proven with features that run as expected.